Geography and Export Performance: External Market Access and Internal Supply Capacity. - Redding, S; Venables, A (CEPR, 2003)
This Paper investigates the determinants of countries' export performance looking in particular at the role of international product market linkages. We begin with a novel decomposition of the growth in countries' exports into the contribution from increases in external demand and from improved internal supply-side conditions. Building on the results of this decomposition, we move on to an econometric analysis of the determinants of export performance. Results include the finding that poor external geography, poor internal geography, and poor institutional quality contribute in approximately equal measure to explaining Sub-Saharan Africa's poor export performance.